Bujang Valley Tourism Co-Creation in place branding: the role of local community / Neesa Ameera Mohamed Salim ... [et al.] - Mohamed Salim, Neesa Ameera; Kula Ismail, Abdullah; Abdul Samat, Syafiq; Nazrin, Nizar (Universiti Teknologi MARA, Perak, 2023)
Despite its well-known reputation for its unique archaeological artefacts’ findings and its historical sites, Bujang Valley or locally known as Lembah Bujang situated in Kedah Malaysia is unable to attract tourists in large numbers, specifically during post Covid-19 pandemic. This study aims to fill the gap by defining the role of local communities in branding Bujang Valley since local community engagement is imperative since they fulfil multiple functions in place branding. 20 locals were approached through convenience sampling for a semi-structured interview in defining their roles and views on the distinctiveness of place identity, culture, economy and hopes as well as their major involvement in the co-creation of the place branding. This exploratory study reveals that the local community are positive and share collective values towards uplifting the brand image specifically in respect to tourism factors, yet the authenticity and the core value should be sustained. The insights gathered provides a novel conceptualization in reproposing a new brand for Bujang Valley. In the future, Bujang Valley should continue to leverage its unique and well-received characteristics, highly considering the direct and indirect roles of the local community towards the process of place branding.